A study on health-related quality of life and comorbidity among elderly population in rural Sabah, Malaysia (South East Asia Journal of Public Health, 2016)
Ageing is a global phenomenon. In Malaysia, a projected model estimated that the number of elderly would be 3.4 million in 2020 which is more than 10% of the population. A cross-sectional study targeted the elderly population of three villages in rural Sabah, Malaysia aimed to investigate the health-related quality of life, comorbidity, and the socio-demographic profile amongst the elderly in the community. Participants (60 years and above) were selected for face-to-face interviews using health-related quality of life questionnaires (SF-36). SPSS 21 was used for statistical analyses. Results showed that mean (sd) of age; 67.71 (6.95) years. Five common co-morbidities were hypertension (67%), bone and joint pain (63%), gastric pain (67%), poor vision (58%), and hearing problems (33%). The highest HRQoL score was social functioning (67.96) whereas the lowest HRQoL score is role limitation due to emotional problems (30.54). There is a significant relationship between HRQoL domains and socio-demographic factors (gender, marital status, membership in association), and health condition (co-morbidities and access to healthcare, bone and joint pain or arthritis and treatment, hearing impairment and treatment) which indicated need for health and social support like participating in association and access to health care for rural elderly in future programme. We recommend a further study to compare elderly HRQoL in rural, urban and institutional settings for future health-care planning.South East Asia Journal of Public Health Vol.5(2) 2015: 35-42